Pengelolaan Arsip Berbasis Aplikasi Surat Di Dinas Perpustakaan dan Kearsipan Provinsi Jawa Timur - Linda Rohmawati; Durinta Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
Office activities today have experienced significant changes. This is caused by the rapid development of technology. Almost all office work and administration are also assisted by existing technology, office work can be done effectively and efficiently. One of the biggest effects of technological advancements in the field of archives at present is the management of electronic records. This study aims to analysis the management of archive applications based on the Letter Application in the Department of Library and Archives of East Java Province. This research is a type of descriptive research with a qualitative approach. Research subjects were two employees in the dynamic records management section. Data collection techniques used were interviews, observation and documentation. The data analysis technique is data collection, data reduction, data presentation and drawing conclusions. Based on research conducted in the field states that the use of the Mail Application is only used as a place to enter data or collect data on incoming and outgoing mail, the application can only be operated with the help of internet access, there are only two employees managing dynamic archives and in managing dynamic archives, namely incoming and outgoing letters are still assisted by disposition sheets and control cards. It can be concluded that the results of this study are the need for application evaluation to develop an electronic records management system that suits the needs of the East Java Province Library and Archives Office so that dynamic archive management will become easier and faster.